2003
DOI: 10.21273/jashs.128.3.0343
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis Procedures for Canopy Spectral Reflectance Data of Seashore Paspalum under Traffic Stress

Abstract: Traffic stresses often cause a decline in turfgrass quality. Analysis of spectral reflectance is valuable for assessing turfgrass canopy status. The objectives of this study were to determine correlations of narrow band canopy reflectance and selected reflectance indices with canopy temperature and turf quality for seashore paspalum exposed to wear and wear plus soil compaction traffic stresses, and to evaluate the effects of the first derivative of reflectance and degree of data smoothing (spectral ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Infrared reflectance is generally high because of cell structure in the leaf (Knipling, 1970; Woolley, 1971). Turfgrass research has examined the effect of irrigation (Fenstermaker‐Shaulis et al, 1997; Park et al, 2005; Baghzouz et al, 2006; Xiong et al, 2007; Dettman‐Kruse et al, 2008), nitrogen (Bell et al, 2002a; Baghzouz et al, 2006; Kruse et al, 2006; Xiong et al, 2007), mowing (Fitz‐Rodriguez and Choi, 2002), disease (Nutter et al, 1993; Green et al, 1998; Raikes and Burpee, 1998; Rinehart et al, 2002), wear (Trenholm et al, 1999; Jiang et al, 2003), traffic (Guertal and Shaw, 2004), cultivars, and species (Jiang and Carrow, 2005, 2007) on reflectance. Repeatedly these studies have found reflectance correlation with turf quality, increased visible reflectance with increasing turfgrass stress, and decreased to variable near‐infrared (NIR) reflectance with increasing turfgrass stress (Nilsson, 1995; Green et al, 1998; Guertal and Shaw, 2004).…”
mentioning
confidence: 99%
“…Infrared reflectance is generally high because of cell structure in the leaf (Knipling, 1970; Woolley, 1971). Turfgrass research has examined the effect of irrigation (Fenstermaker‐Shaulis et al, 1997; Park et al, 2005; Baghzouz et al, 2006; Xiong et al, 2007; Dettman‐Kruse et al, 2008), nitrogen (Bell et al, 2002a; Baghzouz et al, 2006; Kruse et al, 2006; Xiong et al, 2007), mowing (Fitz‐Rodriguez and Choi, 2002), disease (Nutter et al, 1993; Green et al, 1998; Raikes and Burpee, 1998; Rinehart et al, 2002), wear (Trenholm et al, 1999; Jiang et al, 2003), traffic (Guertal and Shaw, 2004), cultivars, and species (Jiang and Carrow, 2005, 2007) on reflectance. Repeatedly these studies have found reflectance correlation with turf quality, increased visible reflectance with increasing turfgrass stress, and decreased to variable near‐infrared (NIR) reflectance with increasing turfgrass stress (Nilsson, 1995; Green et al, 1998; Guertal and Shaw, 2004).…”
mentioning
confidence: 99%
“…Wavelength ( acteristic of canopy structure would be a factor influencing reflectance of seashore paspalum. Jiang et al (2003) found that reflectance from 756 to 804 nm were highly correlated with turf quality of seashore paspalum under wear stress. Trenholm at al.…”
Section: Turf Quality Leaf Firing Grassesmentioning
confidence: 92%
“…These symptoms can be visually rated as a basis of turfgrass drought resistance, but accurate and rapid detection of early symptoms are often difficult and quantitative measurements would be preferred over visual rating. Remote sensing with broad-band spectral reflectance has been used for evaluation of turfgrass performance under drought stress (Fenstermaker-Shaulis et al, 1997;Jiang et al, 2004) and traffic stress (Jiang et al, 2003;Trenholm et al, 1999). This technology provides a rapid, non-destructive estimate of turf quality and could be a possible screening tool for identification of turfgrass stress tolerance.…”
mentioning
confidence: 99%
“…The NDVI (Rouse et al, 1973) has been used in previous turfgrass research to document health status (Trenholm et al, 1999; Jiang et al, 2003, 2009; Jiang and Carrow, 2005; Kruse et al, 2006; Sönmez et al, 2008). In this study, NDVI was evaluated biweekly from June to November using a turf color meter (FieldScout Turf Color Meter 500 NDVI, Spectrum Technologies, Inc., Aurora, IL).…”
Section: Methodsmentioning
confidence: 99%